The Input of the Climatic Factors in the Temperature Regime of Soils of Discontinuous Permafrost of Northern Taiga of Western Siberia - O. Yu. Goncharova; G. V. Matyshak; A. A. Bobrik; D. G. Petrov; M. O. Tarkhov; M. M. Udovenko (Бюллетень Почвенного института им. В.В. Докучаева)
The results of the four-year study of the temperature regime of soils of three common landscapes of northern taiga in Western Siberia, located in the area of discontinuous permafrost, are presented. The soils of lumpy peatlands are characterized by mild permafrost annual regime with very cold summer and moderately cold winter. Temperature regime of the forest soils may be characterized as cold long-time seasonally freezing mild with very cold summer and moderately cold winter. The soils of the investigated region are functioning in conditions of the narrow range of temperatures: at the depth of 20 cm for the soils of all of the landscapes, the temperatures vary within the range of -2.5 to 0°С. This occurs due to their high moisture, low thermal conductivity, specificities of snow cover regime and the freezing effect of permafrost rocks. Annual temperature soil indices are characterized by the weak correlation to the mean annual specificities of air temperature regime. We discovered the direct correlation of annual soil temperature regime and the dynamics of the snow cover (with average and maximal thickness, and thawing date), and with winter N-factor (surface temperature index), and accumulative positive temperatures. Since isolating activity of the vegetation is significantly lower than that of snow (summer N- factors 0.7-0.9), annual fluctuations of summer air temperatures will significantly affect the temperature regime of soils and geo-cryologic situation of the region in general.